Population dynamics of an invasive tree, Sorbus aucuparia, in the understory of a Patagonian forest - Lediuk, Karen Daniela (2016)
Exotic fleshy fruited plants are often dispersed by generalist frugivores into undisturbed or weakly disturbed forests. The establishment and spread of these plants in the understory may pass unnoticed until their abundance and size turns them a nuisance. Sorbus aucuparia is a fleshy fruited tree recently established in temperate forests of northwestern Patagonia. Our aim was to determine the invasion dynamics of S. aucuparia in a Nothofagus pumilio forest. We analyzed age structure, minimum age of reproduction, the time from colonization to effective recruitment (lag time), and demographic parameters to pinpoint critical stages for management. Currently, the population of S. aucuparia is increasing. Large numbers of suppressed, potentially reproductive individuals were found. Lag time was relatively short (25 years) in comparison to other invasive woody plants. The minimum reproductive age was 10 years, and all reproductive individuals were located in high light conditions. The number of trees at the reproductive stage made the most significant contribution to population growth; a 5 % reduction in this number would be enough for the population growth rate to be negatively affected. Thus, the reproductive stage is key to the control of S. aucuparia. Forest disturbance leading to increase light availability may result in higher rates of growth and reproduction among currently suppressed individuals, triggering further expansion events and increasing the number of invasion foci. Management strategies for tree species which present an inconspicuous bank of individuals in the understory, like S. aucuparia, should focus on early detection and eradication of reproductive individuals while avoiding the increase in light availability in the affected environment.